OPTIMIZATION OF RAW MATERIAL SHAFT INSTALLATION AND SPEED ENHANCEMENT IN DPZ CHAINSAW WORKING CHAMBERS (Journal of Science-Innovative Research in Uzbekistan, 2024)
This study focuses on optimizing the installation of the raw material shaft in the working chamber of the DPZ chainsaw and increasing its rotational speed to nhance processing efficiency. The raw material shaft is a critical component of the chainsaw, responsible for feeding raw materials into the cutting mechanism. By improving the installation process and boosting the rotational speed of the shaft, this research aims to reduce downtime, enhance throughput, and improve overall performance in wood processing operations. Through meticulous design modifications, precision installation techniques, and motor upgrades, the goal is to develop an optimized configuration of the raw material shaft that maximizes cutting speed and efficiency in the DPZ chainsaw